THE NARRATION OF RELIGIOUS MODERATION FOR MITIGATING RADICALIZATION AMONG THE MILLENNIAL GENERATIONS ON PESANTREN LIRBOYO INSTAGRAM - Lukman Hakim (Profetik: Jurnal Komunikasi, 2023)
The big idea of religious moderation is a solution to the problem of spreading radical and intolerant views in the millennial generation. Instagram Pondok Lirboyo and Serambi Lirboyo are Islamic boarding schools with many followers with religious moderation content. This study aims to determine the narrative characteristics of religious moderation and the visual communication structure of the millennial generation in the Serambi Lirboyo and Pondok Lirboyo accounts. This study uses qualitative methods through a virtual ethnographic approach. The main object of this study is religious moderation content on Instagram by Pondok Lirboyo and Serambi Lirboyo. Data collection techniques were carried out through participatory observation, interviews, and literature studies. The results are (1) the narrative characteristics of religious moderation emphasize the moral messages of compassion and mutual respect, preaching in a polite manner, and harmony between religion and nationalism. Meanwhile, the narrative form of religious moderation is packaged through past stories, wise sentences from masyayikhs and Islamic leaders, explanations with evidence, and language typical of the millennial generation. (2) The visual communication structure includes lines, shapes, forms, typography, values, and colors. At the same time, the principles of visual communication consist of symmetrical balance, elemental harmony, contrast, and pattern. The formulation of these visual communication components produces exciting content, especially for the millennial generation.